Access to Personal Information for Public Health Research: Transparency Should Always Be Mandatory - Ringuette, Louise; Bélisle-Pipon, Jean-Christophe; Doudenkova, Victoria; Williams-Jones, Bryn (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
In Québec, the Act Respecting Access to Documents Held by Public Bodies and the Protection of Personal Information provides an exception to transparency to most public institutions where public health research is conducted by allowing them to not disclose their uses of personal data (often collected without the consent of those being studied). This exceptionalism is ethically problematic due to important concerns (e.g., protection of privacy and potential harms of secondary uses of data) and we argue that all those who conduct research should be transparent and accountable for the work they do in the public interest.